A meta-analysis of neoadjuvant chemotherapy versus neoadjuvant chemoradiotherapy for locally resectable esophageal cancer based on RCTs - Xu, Tinghui; Wang, Lei; Zhang, Xiaoming; Yu, Xinyan; Zhang, Shiyan; Zheng, Jiamu; Fei, Jie (Frontiers in Oncology, 2026)
BackgroundFor locally resectable esophageal cancer, the efficacy of neoadjuvant chemotherapy (NCT) and neoadjuvant chemoradiotherapy (NCRT) remains controversial. Therefore, this study explores the efficacy difference between NCT and NCRT in locally resectable esophageal cancer (including gastroesophageal junction cancer).MethodsThis study adhered to the guidelines of the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement and was prospectively registered on PROSPERO with the registration number CRD420251044577. Four electronic databases—PubMed, Web of Science, Cochrane Library, and ClinicalTrials.gov—were searched from their inception to May 2025. The primary outcomes of this study were overall survival (OS) and progression-free survival (PFS), which were presented as hazard ratios (HRs) and 95% confidence intervals (CIs). A random-effects model was uniformly used for the pooled analysis and leave-one-out sensitivity analysis and publication bias detection were conducted.ResultsAfter searching and screening, six randomized controlled trials (RCTs) were finally included, involving 886 patients in the experimental group (NCT group) and 877 patients in the control group (NCRT group). The results of statistical analysis show no statistically significant difference in OS (HR = 1.06, 95%CI: 0.85-1.31; p=0.603, I²=59.53%, τ²=0.0411) and PFS (HR = 1.05, 95%CI: 0.79-1.40; p=0.718, I²=76.38%, τ²=0.0892) between NCT and NCRT. Sensitivity analysis reveals that the results remain stable when each study is excluded one by one, and no publication bias is detected using Begg’s test.ConclusionThe results of this study suggest that in the perioperative management of locally resectable esophageal cancer (including gastroesophageal junction cancer), existing data do not yet demonstrate a significant survival advantage for NCRT over NCT. Individualized decision-making is therefore recommended.